SCRATCHING AKULTURASI BUDAYA DI PEDESAAN ACEH SINGKIL - Saputra, Akmal; Triyanto, Triyanto; Juraida, Irma; Khairan, Khairan; Sariyanti, Lilis; Liyana, Cut Irna (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2025)
This research wants to reveal why and how the intercultural acculturation of the Aceh Singkil people after the 2015 religious conflict. This research wants to find new concepts, especially the local values of the Aceh Singkil people so that the religious conflicts that occur can be overcome. The researcher uses Mead's symbolic interactional theory in viewing action (cultural acculturation). In other words, in social interaction, actors are involved in a process of mutual influence. The qualitative method used in this study aims to find out what factors are capable of making the life of the Singkil community very harmonious and to find out the factors that are able to make the plural Singkil community unite and live in harmony. The results of this study show that the factors that scratched the relationship between community members and between religious communities in Suka Makmur Aceh Singkil were the construction of places of worship that did not obtain permission. The establishment of a place of worship that did not get a permit caused the other party to protest and ask for it to be controlled. The factors that make the pluralistic community of Suka Makmur Aceh Singkil able to unite are due to mutual respect and respect as well as the occurrence of cross cutting affiliation as members of the community.